Potencial antitumoral de marsdenia cundurango Reichenbach F. em modelos de carcinoma mamário - Spindola, Daniel Gonsales [UNIFESP] (2018)
Marsdenia cundurango Reichenbach F. is a South American medicinal plant, from the Asclepiadoideae family, popularly used in treatment of stomach cancer, digestive problems and due to its anti-inflammatory and antioxidant actions. The objective of this work was to evaluate antiproliferative and antitumor activity of crude extract of Marsdenia cundurango Reichenbach F. (EBMC) and its chloroform, hexane and dichloromethane fractions obtained from organic solvents in two mammary carcinoma cell lines, MCF7 and 4T1. Cell viability was assessed after 24 hours exposure to EBMC and its fractions by trypan blue exclusion and MTT reduction assays. It was carried out the analysis of the constituents of the EBMC by UHPLC and its antioxidant profile is evaluated by the DPPH method. The incorporation of propidium iodide (PI), double-labeling with Annexin-V-FITC / PI, generation of reactive oxygen species (ROS) and mitochondrial membrane potential by DCF-DA and TMRE, respectively, and evaluation of caspase-3 activation in the 4T1 cell line, both by flow cytometry. Nuclear morphology analysis by Hoechst staining was performed by fluorescence microscopy, and the semi-quantication of Bax and Bcl-2 proteins by Western blotting. The cytosolic calcium increase was evaluated as well as an in vivo assay to evaluate the ability to reduce tumor progression in BALB / c mice. Our results demonstrated that EBMC, but not its fractions, was cytotoxic to MCF7 and 4T1 cells with the ability to reduce cell viability by 50% at a concentration of 100 μg/mL. The characterization of EBMC revealed the presence of active glycosides in it, the Condurangogligosídeos. Cell death assays demonstrated that EBMC increased the sub-G1 fraction and induced cell death, mostly late apoptosis, significantly. EBMC was also able to reduce tumor volume in in vivo assay. In addition, the nuclear morphology analysis revealed the presence of pycnotic nuclei, suggesting the occurrence of cell death. These events were accompanied by increased ROS production, decreased mitochondrial membrane potential, increased levels of Bax protein expression and decreased Bcl-2, and increased cytosolic calcium in both cell lines and activation of caspase-3 in the 4T1 cells. Thus, we conclude that EBMC has induced programmed cell death in MCF7 and 4T1 cells, and it is promising for future studies and clinical applications.